Groundreaction forces from poles and ski in cross country skiing and 3-d kinematics analysis - Canclini, A.; Tagliabue, M.; Pozzo, R.; Moriconi, B.; Bonomi, R.; Baroni, G. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Roveret, 2005)
Introduction: The biomechanics of competitive cross country skiing CCS involve a complex interaction between the kinematics and kinetics parameters of the movement patterns. Despite the complexity of the environment conditions (air and snow temperature, track, techniques, gradients, etc.), several studies were performed to measure the main kinematics parameters (cycle length, frequency, velocity etc.) in the Classical Technique (CT) and in the Skating Free Technique (FT) during high level competition like World Cup races (VIITTASALO `96, MINETTI-CANCLINI 2000). The measurement of forces applied to skis and poles is complicated by the ski equipment and the snow surface. Different approaches were carried out (KOMI 1987, SMITH 1992) with portable and non-portable system, but this last method seems to be not flexible and complicate to use. The aim of this study is to determine the patterns of the main kinematics and kinetics parameters, during simulated races in CT and FT, on different track sections, i.e. on flat terrain and on uphill. Methods: The forces measurements were carried out by means of a self-constructed pressure-insoles, placed on the rear and front part of each foot. The forces applied to the poles were measured by two strain-gauges mounted in the handle of each pole. The data collection were recorded via a portable data-logger at 50 Hz and successively transferred to a PC for analyse. For 3D analysis, two couples of digital camcorders (SONY 50 Hz) were located on two sections of the 2,5 km race track (2 laps): an uphill (12°) 20 meters long section at the 1 km mark, and a flat 40 meters long section at the 2 km mark. Due to the technical requirement of a wide working volume, a dedicated software for video analysis, with free panning, tilting and zooming TV cameras was used (Baroni, 1998). Calibration was performed by means DLT method. The 3-D positions of the control points for system calibration were measured by means of a geodetic theodolite and were marked out with 50 high rigid poles. The biomechanical model of the skier consisted of 17 body landmarks, 6 other points were used for the poles and the skis identification. The total centre of mass (CG) and joints range of motion were calculated with respect to the plane of track (horizontal plane), and to the corresponding orthogonal direction (vertical direction). Four young skiers, from Italian ski team, were analysed while performing the two races of 5 km, one in CT and one in FT, (S.Caterina-I). Results and discussion: Fig. 1 shows a typical stick diagram, the velocity and vertical displacement of CG, in correspondence of the uphill section (Diagonal Stride in CT) and the typical patters of the forces applied to the poles for 3 entire cycles (middle diagram). According with previous works (Smith, 1990; Viitasalo, 1993), the mean values of the cycle time and cycle length were about 1s (0,98±0,06 s) and 3,76±0,26 m respectively. The mean CG velocity was about 3,4 m/s with a vertical displacement less than 10 cm. Fig. 1 (bottom curves) shows a typical patterns of the tibia-ground inclination angles and of the forces applied by each foot on the rear part (PPSX and PPDX respectively for left and right foot) and on the front part (PASX and PADX respectively for left end right foot). The patterns of these forces were founded quite similar to literature data. The kinematics of additional biomechanical parameters is also discussed with reference to the potential significance for the optimisation of the overall movement performance.